STUDY OF CURRENT STATE OF INFORMATIONAL CULTURE FORMATION OF FUTURE NAVIGATORS (Journal of Information Technologies in Education (ITE), 2017)
On the basis of information contained in psychological and educational sources, encyclopaedic and monographic publications and the results of their research of the phenomenon of formation of information culture of future navigators, specified under the direction of research definitions of "test", "index", "meter", "level of formation", " means of diagnosing the levels of ", "method of diagnosing the levels of" criteria, indicators, parameters and methods of diagnosing the state of formation of personality-motivational, cognitive and procedural and operational  components of the information culture of future navigators, color and Author determined high,medium and low levels of its formation, the technique, subject-specific tests and sets objectives for diagnosing the levels of cognitive and procedural and operational components of the information culture of future navigators. Pedagogical planned and carried out the experiment, the results of which revealed the current state of formation of information culture level of future navigators.Statistical analysis of the data pedagogical experiment showed that the experimental group the number of students, information culture which formed at a low level is 46.67 per cent, respectively,in the control - 42.24 percent, the average level of formation of information culture found in 35.83 per cent of students in the experimental group, the control group the figure is 39.66 percent, a high level of formation of information culture inherent in 17.50 per cent of future navigators in the experimental group and 18.1 percent in the control group. Summary of pedagogical experiment showed that the current system of training is not effective in the formation of information culture of future navigators as an integral part of their professional culture that focuses further research to identify and substantiate pedagogical conditions didactic principles, tools and technologies, implementation and the use of which will theoretically justify, develop and implement the system of professional training of future navigators model of their information culture as a component of professional culture navigators.
Keywords: information culture; future navigators; criteria of formation; levels of development; pedagogical experiment